A Novel Ring-Opening/Ring-Closing Cascade Reaction Selectively Induced by Aliphatic Primary Amine Using Phenolic Hydroxyl as a Traceless Directing Group - Huang, Shuntao; Liu, Teng; Li, Jingpeng; Yang, Qi; Zhan, Shuyan; Huang, Chao (Synthesis, 2023)
An interesting ring-closing/ring-opening cascade reaction selectively induced by aliphatic primary amine for the synthesis of functionalized aminomaleimides is described. This work features phenolic hydroxyl as a traceless directing group that forms a critical six-membered intermediate and then a lactone ammonolysis/intramolecular amidation sequence. This two-step, one-pot practical protocol has broad substrate scope (39 examples) and delivers structurally diverse aminomaleimides in good to excellent yields.
Keywords: aminomaleimides; ring-closing/ring-opening reaction; aliphatic primary amines; phenolic hydroxyl; directing group